2002
DOI: 10.1002/gene.10162
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic in vivo imaging of postimplantation mammalian embryos using whole embryo culture

Abstract: Due to the internal nature of mammalian development, much of the research performed is of a static nature and depends on interpolation between stages of development. This approach cannot explore the dynamic interactions that are essential for normal development. While roller culture overcomes the problem of inaccessibility of the embryo, the constant motion of the medium and embryos makes it impossible to observe and record development. We have developed a static mammalian culture system for imaging developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
109
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(111 citation statements)
references
References 9 publications
2
109
0
Order By: Relevance
“…For time-lapse imaging, samples were cultured in a standard tissue culture incubator or on a microscope stage under conditions promoting the culture of mouse embryos (50% rat serum: 50% DMEM buffered with bicarbonate as described by Jones et al, 2002) and maintained under physiological conditions in a closed temperature-controlled, humidified, and oxygenated (95% air, 5% CO 2 ) chamber (Solent Sci, Portsmouth, UK, or custom made). For cytoplasmic counterstaining, samples were incubated for 10 min in Cell Tracker Orange (Molecular Probes, C-2927) at a dilution of 1:500 in dissecting or culture medium.…”
Section: Dissection and Preparation Of Embryos And Adult Tissuesmentioning
confidence: 99%
“…For time-lapse imaging, samples were cultured in a standard tissue culture incubator or on a microscope stage under conditions promoting the culture of mouse embryos (50% rat serum: 50% DMEM buffered with bicarbonate as described by Jones et al, 2002) and maintained under physiological conditions in a closed temperature-controlled, humidified, and oxygenated (95% air, 5% CO 2 ) chamber (Solent Sci, Portsmouth, UK, or custom made). For cytoplasmic counterstaining, samples were incubated for 10 min in Cell Tracker Orange (Molecular Probes, C-2927) at a dilution of 1:500 in dissecting or culture medium.…”
Section: Dissection and Preparation Of Embryos And Adult Tissuesmentioning
confidence: 99%
“…These transgenic mouse lines have been useful in demonstrating a function for visceral endoderm signals in hematopoietic and endothelial development. 27,28 The human ⑀-globin::KGFP transgenic line has permitted dynamic in vivo imaging of the developing yolk sac and circulatory system 29 and quantitative analysis of hemodynamic changes during early embryogenesis. 30 Here, we have used this line to track quantitatively the differentiation and maturation of circulating EryPs during embryogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…In these experiments, embryos were imaged for only minutes up to a few hours. Later, it was shown that robust development of early postimplantation embryos from 5.5-9.5 dpc can be supported on the microscope stage for 18 -30 hr using rich medium and limited evaporation (Jones et al, 2002(Jones et al, , 2004aSrinivas et al, 2004), conditions similar to those required for successful roller culture (Tam, 1998). Early postimplantation embryos are relatively transparent, and many of the dramatic changes that occur in the body plan can be readily imaged.…”
Section: Fluorescence Imaging Of Pre-and Postimplantation Mouse Embryosmentioning
confidence: 99%
“…Live embryo imaging has also been used to study blood flow and dynamic changes in shear stress during vascular remodeling (Jones et al, 2002(Jones et al, , 2004b. Primitive erythroblasts labeled with GFP under the control of the Epsilon-globin promoter (Dyer et al, 2001) have been visualized in cultured 7.5-10.5 dpc embryos using confocal microscopy, providing a simple means to study early circulation and vessel formation (Jones et al, 2002;Fig.…”
Section: Fluorescence Imaging Of Pre-and Postimplantation Mouse Embryosmentioning
confidence: 99%
See 1 more Smart Citation